Doping-Free Complementary Metal-Oxide-Semiconductor Inverter Based on N-Type and P-Type Tungsten Diselenide Field-Effect Transistors With Aluminum-Scandium Alloy and Tungsten Oxide for Source/Drain Contact - Takamasa Kawanago; Ryosuke Kajikawa; Kazuto Mizutani; Sung-Lin Tsai; Iriya Muneta; Takuya Hoshii; Kuniyuki Kakushima; Kazuo Tsutsui; Hitoshi Wakabayashi (IEEE Journal of the Electron Devices Society, 2023)
In this study, we experimentally demonstrated concepts for realizing doping-free Tungsten Diselenide (WSe2) complementary metal-oxide-semiconductor (CMOS) inverter by developing alloys and compound metals used as source/drain (S/D) contacts. Aluminum – scandium alloy (AlSc) and tungsten oxide (WOx)-based S/D contacts enable efficient electron and hole injection into WSe2 for n-type and p-type FET operation because the work function (WF) of AlSc and WOx are aligned to neighboring the conduction and valence band edge of WSe2, respectively. A dual-gate bias architecture is used to improve electrical characteristics of FETs and enhance CMOS inverter performance after device fabrication. By utilizing AlSc and WOx-based S/D contacts in conjunction with the dual-gate bias architecture, our fabricated WSe2 CMOS inverter realized a higher gain at $\text{V}_{ dd}$ of 1 V or higher than those in the literatures. Furthermore, the fabricated WSe2 CMOS inverter is operated at a power supply voltage ( $\text{V}_{ dd}$ ) of as low as 0.5 V. This study paves the way towards research and development of transition metal dichalcogenides-based devices and circuits.